The role of universities in development - Duga, Zsófia; Szontágh, Krisztina (REGIONAL AND BUSINESS STUDIES, 2011)
Innovations play a more and more important role in the economic development of each region. The success of the regions’ developmental strategy depends in large part on resources and the geographic location of those resources within the region. Universities play a definitive role in regional development. The University of Pécs is one of the largest and most popular higher education institutions in Hungary. Over 32,000 students study at its ten faculties and its staff numbers more than 6,000. As reflected in the number of its faculties, the University embraces almost the full spectrum of higher education. It includes training programmes in law, health care, economics, natural sciences, humanities, technology, arts, pedagogy, and adult education. There are over 100 majors and specialties that preserve traditional forms of training while adapting to better suit current social and economic needs. The university, as a key participant in economic life and development, can help foster cooperation in the business sphere and assist local municipalities and the central government in regional development programmes. In my presentation I wish to introduce the role of the University of Pécs in the development of the Transdanubian Region and the ways it may join in regional development programmes through education, research, and scientific activity. Keywords: region, universities, companies, innovation, R&D